2019
DOI: 10.1007/s40093-019-00304-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of compost formulation and postharvest management on quality parameters of button mushroom

Abstract: Purpose The main objective of the present study was to evaluate the effects of compost formulation made from agricultural by-products and thermal treatment of fresh mushrooms on the postharvest quality parameters. Methods Quail manure was evaluated as an alternative ingredient to the broadly used chicken manure for compost preparation. In addition, the treatment of fresh mushrooms by hot water to extend shelf-life was tested. Quality parameters including color (browning due to microbial activity), cap opening … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 18 publications
(23 reference statements)
0
6
0
Order By: Relevance
“…Ranjbar et al . (2019) also reported that button mushrooms harvested from quail manure compost exhibited a higher L* value, indicating a whiter appearance, compared to those harvested from chicken manure compost. Additionally, compost used for mushroom production can also affect the post‐harvesting changes.…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations
“…Ranjbar et al . (2019) also reported that button mushrooms harvested from quail manure compost exhibited a higher L* value, indicating a whiter appearance, compared to those harvested from chicken manure compost. Additionally, compost used for mushroom production can also affect the post‐harvesting changes.…”
Section: Resultsmentioning
confidence: 94%
“…Ranjbar et al . (2019) noted that mushrooms cultivated on chicken manure maintained their whiteness for longer storage duration than those grown on quail manure.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Microorganisms play an important role in high-yielding production of A. bisporus. Compost preparation is a critical step in the cultivation process, where the biochemical transformations that take place during composting, provide the nutrients that determine mushroom growth [7][8][9]. Viera and Pecchia (2018) and many other authors [11,12] described the influence of pasteurization conditions of compost, and additives or external microorganisms on the composition of the fungal growth and the fruiting environment.…”
Section: Discussionmentioning
confidence: 99%